2023
DOI: 10.3390/pharmaceutics15030799
|View full text |Cite
|
Sign up to set email alerts
|

Hot Melt Extruded Posaconazole-Based Amorphous Solid Dispersions—The Effect of Different Types of Polymers

Abstract: Four model polymers, representing (i) amorphous homopolymers (Kollidon K30, K30), (ii) amorphous heteropolymers (Kollidon VA64, KVA), (iii) semi-crystalline homopolymers (Parteck MXP, PXP), and (iv) semi-crystalline heteropolymers (Kollicoat IR, KIR), were examined for their effectiveness in creating posaconazole-based amorphous solid dispersions (ASDs). Posaconazole (POS) is a triazole antifungal drug that has activity against Candida and Aspergillus species, belonging to class II of the biopharmaceutics clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The increase of amorphousness of the polymer enhanced the physical stability of the ASDs. Compared to homopolymers, the ASDs formulated with copolymers exhibited greater homogeneity but less enhancement in aqueous solubility [270] .…”
Section: Manufacturing Asdsmentioning
confidence: 95%
See 2 more Smart Citations
“…The increase of amorphousness of the polymer enhanced the physical stability of the ASDs. Compared to homopolymers, the ASDs formulated with copolymers exhibited greater homogeneity but less enhancement in aqueous solubility [270] .…”
Section: Manufacturing Asdsmentioning
confidence: 95%
“…constructed thermodynamic phase diagrams for ASD systems and utilized them to guide HME process [269] . They found that this approach ensured the desired quality of ASDs [269] .The type of polymers can affect the miscibility and homogeneity of ASD prepared by HME [270] . Kramarczyk et al.…”
Section: Manufacturing Asdsmentioning
confidence: 97%
See 1 more Smart Citation
“…The value of this blend’s viscosity was between 10 3 and 10 4 Pa⋅s, in the suitable range that was also determined by other researchers beforehand. [ 59 ].…”
Section: The Use Of Pva In 3d Printing Technologymentioning
confidence: 99%
“…POS showed a sharp endothermic peak at 170.3 • C, indicating the melting point and crystalline nature of the POS. Kramarczyk et al [25] described this endothermic peak as the melting event of POS polymorphic form I, which is anhydrous. A small peak before the melting of drug, at 109.7 • C, indicated nematic phase transition, which is characteristic of POS and other triazoles [26].…”
Section: Solid Dispersion Of Posaconazolementioning
confidence: 99%